Molecular Detection of IntegronclassI Gene in Pseudomonas Aerginosa Isolated from Otitis Media - Ridha Abbas Al-Fahham, Hala (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to investigate the Pseudomonas aeruginosa from patients suffering from otitis media infection. The study included the bacterial diagnosis based on reliable diagnostic procedures. A total of 40 specimens were collected from ear swabs in Al-Najaf province within the period from September to December 2019. These patients ranged from 30 to 75 years. The male more than the female. Primary identification depended on Gram staining and biochemical tests. Finally, identification with the Vitek 2 system was done; the results demonstrate the 30 (75%) Pseudomonas aeruginosa. Genetically, study the gene encoding integrin of P. aeruginosa by using the PCR technique. The results indicated that all P. aeruginosa isolates contain the IntClassI gene; PCR amplification revealed that 30 (75%) of P. aeruginosa carried the int1 gene.